Taxonomy‐based testing and validation of a new defect classification for health software. Issue 1 (15th August 2018) - Rajaram, Hamsini Ketheswarasarma; Loane, John; MacMahon, Silvana Togneri; Mc Caffery, Fergal
Abstract: Defect‐based testing is a powerful tool for finding errors in software. Many software manufacturers avoid this method because it requires a detailed defect taxonomy that is expensive to construct and difficult to validate. The Association for the Advancement of Medical Instrumentation is developing SW91, * a defect taxonomy to be published as a standard for health software. This paper details three methods to validate SW91 for its comprehensiveness. The initial validations of SW91 were conducted via mapping vulnerabilities from the common weakness enumeration and a dataset from a medical device software development company in Ireland. Taxonomy‐based testing is another validation method proposed in this research, and its applicability was investigated using empirical data from a medical device software development company in Ireland. Finally, the paper details future plans to implement taxonomy‐based testing to improve software quality in medical device software and to validate SW91. This validation will focus on the efficiency, reliability, and ability to perform useful analyses and defect coverage of SW91.